فعالية استراتيجية الاستجابة البدنية الكلية في تحسين نتائج تعلم المطالعة لدى طالبات الصف الثالث بمعهد الهجرة نجاوى - Budhi Agustian, Sekar; Nurlaila, Riza (Himpunan Mahasiswa Program Studi (HMPS) Pendidikan Bahasa Arab Fakultas Tarbiyah dan Ilmu Keguruan (FTIK) Institut Agama Islam Negeri (IAIN) Jember, 2026)
The results of mutholaah learning among third-year female students at Ma’had Al-Hijrah Najawi are still low due to the use of traditional teaching methods with limited interactive activities, which causes students to feel bored. Some previous studies have discussed the Total Physical Response (TPR) strategy in language teaching. This study aims to examine the effectiveness of using the Total Physical Response (TPR) strategy in improving mutholaah learning outcomes and to compare learning outcomes between the experimental class and the control class. This study used a quantitative method with a quasi-experimental design involving a control group with pre-test and post-test. The sample consisted of 28 students divided into an experimental class and a control class. The results showed a statistically significant difference, where the experimental class obtained a higher mean score (87.36) than the control class (70.36), indicating that the Total Physical Response (TPR) strategy is effective in improving mutholaah learning outcomes.